Kapasitas Perpustakaan dalam Mendukung Pendidikan Inklusi di UIN Sunan Kalijaga Yogyakarta - Muh Khabib; Anik Nur Azizah (Perpustakaan Nasional, 2024)
UIN Sunan Kalijaga Yogyakarta Library as a task implementing unit is an integral part of UIN Sunan Kalijaga Yogyakarta in supporting inclusive education. The purpose of this study is to describe the programmes and activities that have been carried out by the UIN Sunan Kalijaga Yogyakarta Library that have been running. This paper is compiled based on best practice with data collection using three methods, first participatory observation method, second using interview method, and third using documentation method. The library has an important role in supporting inclusive education by applying aspects of organizational capacity. The aspects of organizational capacity applied at UIN Sunan Kalijaga Yogyakarta Library are 1) aspects of human resources, 2) aspects of infrastructure, technology and financial resources, 3) aspects of strategic leadership, 4) aspects of program and process management, 5) aspects of cooperation and relationships with other parties. After the analysis, it can be concluded that the capacity of UIN Sunan Kalijaga Yogyakarta Library related to supporting inclusive education has been well implemented in accordance with the existing aspects. Of the five aspects, what still needs to be improved is the aspect of human resources, which is related to the quantity/number of librarians at UIN Sunan Kalijaga Yogyakarta Library.